Perspektif Sosio-Historis tentang Menata ke Depan Keunggulan Pendidikan Islam - Bahaking Rama (Al-Musannif, 2020)
This article discusses four things: 1) the challenges of Islamic education, 2) the problems of education in Indonesia, 3) the socio-historical Islamic education in Indonesia, and 4) managing the superiority of Islamic education in the future. This research is descriptive qualitative with conceptual analysis method. Data collected through library documentation are then processed and analyzed using content analysis method. The results of the study show that the main challenges of Islamic education are the dichotomy of science and the dualism of education that influence the orientation and epistemology of Islamic education. The main problem of education in Indonesia is the purpose of education is not optimally supported by other educational factors, while the morale of the nation's children has degraded with increasingly complex delinquency. Socio-historically, the socio-religious interaction of the community can form a distinctive educational tradition by combining Islamic (religious) and national (cultural) values ​​without ignoring the development of the times. The future of Islamic education is largely determined by the awareness, sincerity, and power of the jihad of its educators, as well as the sincerity of the government in applying Islamic teachings in various jobs and all aspects of life.